Equity Ownership Strategy in Greenfield Investments : Influences of Host Country Infrastructure and MNE Resources in Emerging Markets - Arslan, Ahmad; Larimo, Jorma; Dikova, Desislava (Palgrave Macmillan, 2019)
This chapter addresses equity ownership strategy in greenfield investments by multinational enterprises (MNEs) in the emerging markets (EMs). It is one of the few studies to hypothesize and analyze influences of host EM physical infrastructure in relation to investment decisions of MNEs. We use resource dependence theory (RDT) as a theoretical basis and test the moderating effects of firm resources like size and host country investment experience. Moreover, the current study assumes a more nuanced approach to studying equity ownership by analyzing wholly owned subsidiaries versus joint ventures (JVs) and including majority versus minority JVs in the analysis as well. The empirical results based on greenfield investments undertaken by Nordic (Danish, Finnish, Norwegian, and Swedish) MNEs in EMs during 1990–2015 reveals the importance of host country physical infrastructure for high equity ownership strategy. Moreover, host country investment experience moderates the effect of physical infrastructure on equity ownership strategy. Finally, the analysis of a sub-sample of greenfield JVs reveals that determinants of equity ownership strategy differ somewhat between greenfield JV or greenfield wholly owned subsidiaries (WOS).
Keywords: Equity ownership; Greenfield investments; MNE size; MNE host country investment experience; Host country physical infrastructure; emerging markets; fi=Kansainvälinen liiketoiminta|en=International Business|